Myocarditis in malaria—current evidence and future directions: a literature review - Gbolahan Olatunji; Emmanuel Kokori; Ikponmwosa Jude Ogieuhi; Olumide Akinmoju; Oluwatobi Omoworare; Doyin Olatunji; David Timilehin Isarinade; God-dowell O. Odukudu; Israel Charles Abraham; Samuel Owolabi; Jamil Nasrallah; Emmanuel Egbunu; et al. (The Egyptian Journal of Internal Medicine)
Abstract Malaria, though witnessing a decline in prevalence, remains a global health threat. Despite its primarily recognized impact on the hematological system, recent studies shed light on severe cardiac complications, particularly myocarditis, associated with Plasmodium infections. This review examines the literature on malaria-induced myocarditis to elucidate its mechanisms, clinical manifestations, regional perspectives, treatment outcomes, and diagnostic challenges. A literature search spanning PubMed, Scopus, and Web of Science identified relevant studies up to January 2024, encompassing case reports, cohort studies, clinical trials, and experimental studies. The relationship between severe malaria and myocardial involvement is explored, showcasing elevated biomarkers indicative of myocardial damage. Notably, while Plasmodium falciparum is traditionally linked to malaria-induced myocarditis, instances of Plasmodium vivax contributing to cardiac complications are documented. Regional perspectives reveal diverse cases, emphasizing the importance of considering malaria-induced myocarditis in endemic regions and beyond. Treatment outcomes underscore the efficacy of timely antimalarial therapy, advocating for integrated approaches to patient care. Diagnostic challenges, often complicated by overlapping symptoms with other cardiac conditions, highlight the need for heightened clinical suspicion. Addressing therapeutic challenges involves balancing antimalarial drugs, supportive care, and long-term monitoring. Future research directions are outlined, emphasizing the necessity for understanding host-parasite interactions, elucidating molecular mechanisms, and developing targeted diagnostic tools. This review consolidates the current knowledge on malaria-induced myocarditis, emphasizing the significance of continuous vigilance, research, and improved diagnostic approaches to mitigate the impact of this overlooked complication.